Benchmarking of management accounting best practices as an alternative continuous improvement activity in health service organisations: the case of Malaysian hospitals in the northern region / Zubir Azhar …[et al.] - Azhar, Zubir; Abdul Rahman, Ibrahim Kamal; Abdul Rahman, Nor Hafizah; Ismail, Noridah; Radjeman, Leily Adja (Research Management Institute, 2010)
This paper describes the use of some management accounting technologies in three Malaysian hospitals in the Northern region. Results of interviews with decision support specialists and medical experts revealed their focus of practices on strategic management accounting (SMA). Survey responses were also sought from each hospital delineating basic organisational information and detailed data on SMA practices through questionnaire distribution. Our attention is focused on the benchmarking of management accounting best practices of these hospitals to derive a set of outstanding practices that can serve as bases for possible adoption by other health service organisations. Comparative analysis is presented to show differences of SMA application in individual hospital setting. The fundamental differences between the model hospital and two other hospitals have been identified mainly on the managerial approaches and the extent of application of SMA in managing business operations and improving decision-making functions. The model hospital has been identified based on merit of best practices in its business solution. Desirability of individual hospitals towards SMA is separately analysed with emphasis on areas or functions of application. We engaged a case study approach with heavy reliance on formal interview and survey responses from key decision makers and informal interviews with supporting staff of the hospitals to understand their management accounting practices. Secondary data from annual reports, internal reports and media releases have also been sought to enhance the desirability of the findings discussed. Our findings revealed that the extent of SMA practices of model hospital exceeded those of two other hospitals. Although we notice that every hospital under study places emphasis on SMA technologies, phenomenal practices of the model hospital are evident. Its seriousness and continuous application of SMA technologies particularly of those sophisticated ones should be taken as yardstick for possible replication or reference by other health service organisations. At the end of this paper, we proposed a benchmarking model that concerns some areas or functions whereby competitive search of outstanding managerial practices in health service organisations is greatly emphasised. We have constructed a benchmarking model based on the needs to undertake benchmarking as a continuous improvement activity in health service organisations. This is directed towards helping others in achieving the desired business results by strategically positioning themselves into SMA practices in making informed decisions in their business undertakings. This paper also examines issues and challenges confronting these hospitals and assesses the potential role of incorporating SMA in their practice despite the reforms of individual hospitals.